2008
DOI: 10.1128/jb.00760-08
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Comparison of Ribosomal Operon Antitermination Function

Abstract: Transcription antitermination in the ribosomal operons of Escherichia coli results in the modification of RNA polymerase by specific proteins, altering its basic properties. For such alterations to occur, signal sequences in rrn operons are required as well as individual interacting proteins. In this study we tested putative rrn transcription antitermination-inducing sequences from five different bacteria for their abilities to function in E. coli. We further examined their response to the lack of one known rr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…This mutation strongly reduced the intensity of the domain boundary at the van locus; however, transcription of this mutant rsaA (ATG→TAA) was severely diminished, likely due to Rho‐dependent transcription termination (Figs and EV3B–D). Thus, to retain high levels of transcription while preventing translation, we inserted a Caulobacter anti‐termination sequence (Arnvig et al , ) into the leader sequence of rsaA . RT–PCR analysis confirmed that rsaA transcription in this strain (anti‐termination + ATG→TAA) was restored to near wild‐type levels (Fig EV3B–D), and S‐layer protein extraction confirmed the absence of rsaA translation (Fig EV3E).…”
Section: Resultsmentioning
confidence: 99%
“…This mutation strongly reduced the intensity of the domain boundary at the van locus; however, transcription of this mutant rsaA (ATG→TAA) was severely diminished, likely due to Rho‐dependent transcription termination (Figs and EV3B–D). Thus, to retain high levels of transcription while preventing translation, we inserted a Caulobacter anti‐termination sequence (Arnvig et al , ) into the leader sequence of rsaA . RT–PCR analysis confirmed that rsaA transcription in this strain (anti‐termination + ATG→TAA) was restored to near wild‐type levels (Fig EV3B–D), and S‐layer protein extraction confirmed the absence of rsaA translation (Fig EV3E).…”
Section: Resultsmentioning
confidence: 99%
“…As CRISPR transcripts are not translated, it is likely that special antitermination mechanisms exist to ensure efficient transcription of CRISPR RNA. In the case of rDNA transcription, a poorly characterized antitermination system that relies on an upstream rut element ensures efficient production of full‐sized transcripts (Arnvig et al ., 2008). No sequences matching the rut sequence are present in CRISPR transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…While the addition of the strong Ptet promoter did enhance gene silencing by distal spacers ( Figure 2B), gene silencing polarity within the MC arrays was still not fully overcome ( Figure 3), indicating that additional factors likely influenced crRNA production. BoxA elements are often found upstream of long non-coding RNAs, like the 16S RNA (35), where they are bound by the Nus complex to prevent Rho-dependent transcription termination (36)(37)(38). Stringer et.…”
Section: Boxa Elements Reduce Polarity Of Spacer Transcription To Promentioning
confidence: 99%